ANALISIS KESALAHAN MAHASISWA PROGRAM STUDI MANAJEMEN INFORMATIKA UNIVERSITAS PUTRA INDONESIA “YPTK” PADANG DALAM MENYELESAIKAN SOAL-SOAL STATISTIKA DAN PROBABILITY - Syelfia Dewimarni (PHI: Jurnal Pendidikan Matematika, 2017)
This research is qualitative descriptive research. Purpose of this research is to describe student’s mistake in doing exercise in hypotheses testing material, regression and correlation analysis, and probability basic concept in statistics subject and probability. Sample  in this research is student in program study of information and technology management of UPI “YPTK” Padang in second semester academic year of 20162. Data collecting method is using a test by going exercise about hypotheses testing material, regression and analysis and correlation, and probability basic concept. Type of  the exercise is descriptive, then student’s answer analyzed to find mistake made by student’s in doing these exercise. Mistake that would be analyzed are common mistakes and mostly more by students in answer the question about hypotheses testing, regression and correlation, and probability basic concept. Based on the research result, it can be concluded : (1) Students did not make interpretation toward the result gathered after finish doing exercise about hypotheses testing (2) There was an inclination of students to make mistakes in substituting the result value into a term in doing exercise about regression analysis material and correlation (3)Students make mistakes in seeing credibility interval table and in doing exercise About probability basic concept.Keywords : Mistakes Analysis, Statistics and Probability, UPI “YPTK” Padang.